Study protocol for an International Prospective Observational Cohort Study for Optimal Bowel Resection Extent and Central Radicality for Colon Cancer (T-REX study) - Shiozawa, Manabu; Ueno, Hideki; Shiomi, Akio; Kim, Nan Kyu; Kim, Jin Cheon; Tsarkov, Petr; Grützmann, Robert; Dulskas, Audrius; Liang, Jin Tung; Samalavičius, Narimantas; West, Nick; Sugihara, Kenichi (Japanese Journal of Clinical Oncology, 2021)
This is a prospective observational cohort study aiming to include 4000 patients with stages I to III colon cancer treated at 35 specialist institutions in Japan, South Korea, Germany, Russia, Lithuania and Taiwan. The anatomical distribution of lymph nodes and feeding arteries are investigated using surgical specimens according to pre-specified categorizing methods using intraoperative anatomical markings. Primary analyses are performed to identify the general principles of metastatic lymph node distribution in terms of its relation to the location of the primary tumor and feeding arteries. Secondary analyses will be used to estimate prognostic outcomes according to bowel resection length and central radicality and will be used to evaluate the quality of resected surgical specimens. Through in-depth lymph node mapping, standardized criteria for the definite area of 'regional' lymph node resection in routine surgical procedures can be identified, which is expected to contribute to international standardization in colon cancer surgery (ClinicalTrials.gov NCT02938481).
CRIS-Team Scopus Importer:2021-01-15
Keywords: bowel resection margin; complete mesocolic excision; D3 dissection; lymph node mapping; lymphadenectomy